2004
DOI: 10.1002/uog.1077
|View full text |Cite
|
Sign up to set email alerts
|

Maxillary length at 11–14 weeks of gestation in fetuses with trisomy 21

Abstract: Objective To determine the value of measuring maxillary length at 11-14 weeks of gestation in screening for trisomy 21. Methods

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(50 citation statements)
references
References 12 publications
2
47
0
1
Order By: Relevance
“…A short maxillary length has been associated with trisomy 21 [23]. Micrognathia can be detected as an isolated structural anomaly, as one of the features of a chromosomal abnormality, or a syndrome [24].…”
Section: Facial Abnormalitiesmentioning
confidence: 99%
“…A short maxillary length has been associated with trisomy 21 [23]. Micrognathia can be detected as an isolated structural anomaly, as one of the features of a chromosomal abnormality, or a syndrome [24].…”
Section: Facial Abnormalitiesmentioning
confidence: 99%
“…Fetuses with trisomy 21 were shown to have shorter maxillary length [7]. Unfortunately, this was not found to be clinically useful as the two-dimensional (2D) maxillary length measurement was not reliable (as the ramus and condylar process can often overlap increasing the measurement) and the difference between euploid and trisomy 21 fetuses is small enough to be within the axial resolution of most ultrasound systems [8].…”
Section: Introductionmentioning
confidence: 99%
“…The midfacial hypoplasia in Down syndrome can be shown by the shorter maxillary length, absent nasal bone, and frontomaxillary facial angle, which was significantly greater in fetuses with trisomy 21 than in euploid fetuses. [18][19][20][36][37][38][39] In fetuses with trisomy 18, it was reported that the frontomaxillary facial angle was greater and the mandibulomaxillary facial angle was smaller than those in normal fetuses because of midfacial hypoplasia and micrognathia or retrognathia. Fetal alcohol syndrome is characterized by evidence of growth restriction, neurodevelopmental abnormalities, and a characteristic pattern of facial anomalies, such as short palpebral fissures, midfacial hypoplasia, a smooth philtrum, minor ear anomalies, and micrognathia.…”
Section: A B Cmentioning
confidence: 99%